Managing with fire: effects of recurring prescribed fire on soil and root-associated fungal communities - Oliver, Alena K. (Kansas State University, 2020)
Prescribed fire is a necessary management tool used to reduce fuel loads and to maintain fire-adapted ecosystems over time. Although the effects of fire on vegetation and soil properties are well understood, the long-term impacts of different fire regimes on soil fungi, root-inhabiting and ectomycorrhizal (ECM) fungi remain largely unknown. Previous studies show that high intensity wildfires reduce soil fungal biomass and alter fungal communities, however the effects of repeated low intensity prescribed fires are less understood. Studies described in this thesis took advantage of a long-term (>25 years) fire management regime in southern yellow pine stands in the southeastern United States to analyze the effects of repeated prescribed fires on soil fungi, root-associated and ECM fungal communities. The fire management regimes included five fire treatments varying in season (winter and summer) and interval length (two-year, three-year, six-year, and unburned control) allowing us to address effects of burn season and fire frequency on these fungal communities. We used 454-pyrosequencing to analyze ECM roots to specifically focus on the root-associate fungi and ECM. After a pilot study comparing the use of non-proofreading and proofreading polymerases to generate deep high throughput sequence data on soil fungal communities using Illumina MiSeq technology, proofreading polymerase was chosen to create amplicon libraries to minimize overestimation of community richness and underestimation of community evenness. We found that season had no or only minimal effect on diversity and community composition on any of these fungal communities. However, both soil and root-associated fungi responded compositionally to frequent fire intervals. In contrast, we observed no effects of recurring fire on ECM communities. Indicator taxon analyses identified many taxa in each dataset (soil, root-associated, and ECM fungi) that represent potentially fire suppressed or fire adapted taxa. These findings indicate that frequent recurring prescribed fires result in distinct fire adapted/tolerant soil and root-associated fungal communities that are correlated with the desired fire-adapted plant communities. However, the ECM symbionts colonizing these hosts remain largely unaffected.
Keywords: Fungal ecology; Fire effects; Southern yellow pine; Ecology (0329)